GOOD CORPORATE GOVERNANCE (GCG) ON PT. BANK RAKYAT INDONESIA (Persero) Tbk. - Endratmoko (Dinasti International Journal of Education Management And Social Science, 2020)
To implement GCG (good corporate governance), companies must have standard limits, namely ethics and regulations to achieve success. Where ethics provides awareness for companies to run businesses that prioritize business ethics when dealing with stakeholders and to avoid conflicts. As for regulations, companies are required to implement and comply with statutory regulations. The purpose of implementing GCG is to conduct business with sound practices, in order to realize the company's goals in achieving its vision and mission by taking into account shareholders and stakeholders. The writing of this article uses descriptive qualitative methods to analyze and compare theories with implementation in the world of work or based on empirical experience so that researchers can identify information as deeply as possible and as carefully as possible to analyze the application of GCG (Good Corporate Govenance) at PT Bank Rakyat Indonesia ( Persero) Tbk. The results of this study indicate that the application of GCG in BRI companies applies the principles of GCG (Good Corporate Governance) which include: Accountability, Responsibility, Independence, Transparency, and Fairness.